DRAWING-BASED WRITING TASK TECHNIQUE TO IMPROVE YOUNG EFL LEARNERS’ DESCRIPTIVE TEXT WRITING SKILLS - Jasrial, Dedi; Burhan, Kristian; Sepyanda, Marsika (Universitas Mahaputra Muhammad Yamin, 2025)
Teaching writing to young learners in an English as a Foreign Language (EFL) context often met with concerns about developmental readiness. However, some studies show that young learners can benefit from creative and multimodal approaches to writing. While much has been studied on teaching speaking and listening skills, studies on visual stimuli like drawing for writing instruction at an early age are limited. This study aims to empower young learners to produce simple descriptive texts through a drawing-based writing task, using their favorite pets as the topic. Employing a case study design, this study involved one class of children, class I,I, which consisted of fourteen learners in a private English language course in Bengkulu, Indonesia. They were in the first and second grades in the elementary schools with ages between 6-7 years. Data were collected through classroom observations, student work, and reflective feedback from teachers. After young learners studied basic vocabulary and sentence structures in eight meetings, they drew their favorite pets and wrote short descriptions based on their drawings. The number of sentences that they should write ranges from four to six sentences. Each sentence contained five to eight words. The results show that young learners could write simple descriptive texts using basic vocabulary and sentence structures using drawing-based writing tasks. This technique also helped young learners generate content and reduced cognitive load during writing. These findings suggest that creative, visual-based tasks can be effective in teaching writing to young EFL learners.